The game narrative toolbox - Heussner, Tobias (Burlington, MA Focal Press, 2015)
Learn how to create compelling game storylines. Four experienced narrative designers from different genres of game development have banded together to create this all-inclusive guide on what it's like to work as a writer and narrative designer in the videogame industry. From concept to final testing, The Game Narrative Toolbox walks readers through what role a narrative designer plays on a development team and what the requirements are at every stage of development. Drawing on real experiences, authors Tobias Heussner, Toiya Finley, Ann Lemay, and Jennifer Hepler provide invaluable advice for writing compelling player-centered stories and effective dialogue trees in order to help readers make the switch from prose- or screen- writing to interactive. Accompanying every chapter are exercises that allow the reader to develop their own documentation, outlines, and game-dialogue samples for use in applying for industry jobs or developing independent projects. This first installment of Focal Press's Game Design Workshops series is a must-have for individuals looking to create captivating storylines for games
Keywords: Videojuegos